Are We In or Are We Out? Ingroup Prototypicality Effects in Implicit Ethnic‐American Associations. (25th October 2018) - Devos, Thierry; Anderson, Kristin J.
Abstract: The goal of the present research was to document ingroup prototypicality effects in implicit associations between ethnic groups and the American identity. Across four studies, we compared implicit associations displayed by perceivers who either belonged to or did not belong to the target ethnic groups. In Studies 1 and 2, African, Asian, Latino, and European American participants were randomly assigned to complete an Implicit Association Test contrasting either their ingroup and an outgroup or two outgroups (third‐party perspective). Data yielded evidence for ingroup prototypicality effects in all interethnic comparisons. Studies 3 and 4 used large datasets available through Project Implicit. We examined whether ingroup prototypicality effects were restricted to U.S. residents or generalized to participants living in other regions of the world. Results showed that ingroup prototypicality effects did not presuppose immersion in the U.S. context, but at the same time patterns of implicit associations varied according to region of residence. Implicit ethnic‐American associations are at least partially the reflection of the perceivers' positioning in interethnic comparisons.